KANDUNGAN ORGANIK LIMBAH CAIR INDUSTRI BATIK JETIS SIDOARJO DAN ALTERNATIF PENGOLAHANNYA (Jurnal Kajian Lingkungan, 2014)
Liquid waste generated by batik industry in Sidoarjo Jetis directly discharged into water bodies will increase the concentration of COD, BOD, TSS, pH, Sulfide, Ammonia, Chromium, Phenols, Oils and Fats. The purpose of the study was to determine the concentration of COD, BOD, TSS, pH, Sulfide, Ammonia Total, Total Chromium, Phenols, Oils and Fats in Sidoarjo Jetis River. Batik effluent sampling carried out by the grab. Analysis example with pHmeter, Gravimetry, Reflux, Winkler, Iodometry, Kjeldahl, AAS and spectrophotometry. Sampling taken at the drain of industrial production process of batik. Laboratory test results exceeded the water quality standard of waste textile waste according to SK. Governor of East Java, 45 in 2002, pH, TSS = 160.00 mg/l, COD = 400.00 mg/l O2, BOD = 164 mg/l, Oils and Fats = 600.00 mg/l. Appropriate alternative for wastewater treatment with the. sewage treatment system uses a combination of alum and biological physics, namely the processing of coconut shell charcoal adsorbent and Anaerobic Baffle Reactor (ABR). ABR is able to separate the COD up to 98 %, physics processing can reduce levels of COD, Mn for 6 hours and 60 minutes for sedimentation time coagulant concentration of 50 ppm is equal to 67.05 % and coconut shells to remove the color.Keywords: Liquid Waste Batik, Coagulant, Coconut Shell Charcoal, Anaerobic Baffle Reactor